2011
DOI: 10.1093/mp/ssr067
|View full text |Cite
|
Sign up to set email alerts
|

Live-Cell Imaging of Dual-Labeled Golgi Stacks in Tobacco BY-2 Cells Reveals Similar Behaviors for Different Cisternae during Movement and Brefeldin A Treatment

Abstract: In plant cells, the Golgi apparatus consists of numerous stacks that, in turn, are composed of several flattened cisternae with a clear cis-to-trans polarity. During normal functioning within living cells, this unusual organelle displays a wide range of dynamic behaviors such as whole stack motility, constant membrane flux through the cisternae, and Golgi enzyme recycling through the ER. In order to further investigate various aspects of Golgi stack dynamics and integrity, we co-expressed pairs of established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…In addition, one of the matrix protein, AtCASP, did not fully relocate to the ER but localized to small punctate structures colocalizing with ERES (Schoberer et al, 2010). On the other hand, we and other have shown that both cis-and trans-Golgi cisternae collapse almost at the same time in tobacco BY-2 cultured cells (Ito et al, 2012;Madison and Nebenführ, 2011). Moreover, we have demonstrated that AtCASP relocalizes to the ER almost completely by BFA treatment (Ito et al, 2012).…”
Section: Golgi Regeneration After Bfa Treatmentmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, one of the matrix protein, AtCASP, did not fully relocate to the ER but localized to small punctate structures colocalizing with ERES (Schoberer et al, 2010). On the other hand, we and other have shown that both cis-and trans-Golgi cisternae collapse almost at the same time in tobacco BY-2 cultured cells (Ito et al, 2012;Madison and Nebenführ, 2011). Moreover, we have demonstrated that AtCASP relocalizes to the ER almost completely by BFA treatment (Ito et al, 2012).…”
Section: Golgi Regeneration After Bfa Treatmentmentioning
confidence: 62%
“…Scale bar, 5 mm. go forward and the stacks sometimes roll to change the leading side (Madison and Nebenführ, 2011). Microtubules, the other major cytoskeletal system, is not required for long-range movement of the plant Golgi stacks, because the treatment by microtubule disrupting drugs such as nocodazole, colchicine, and propyzamide does not have significant effects (Nebenführ et al, 1999).…”
Section: Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also observed the behavior of ATCASP, which did not fully distribute to the ER by BFA treatment. Madison and Nebenführ (2011) also examined the effect of BFA on Golgi proteins in BY-2 cells. Both cis - and trans -cisternae fused with the ER upon BFA treatment, but no significant difference was found for different cisternae.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy seedlings were selected and the cotyledons were analyzed by the abaxial side on the confocal microscope. Markers expressed using this system were ManI-YFP (Madison and Nebenführ, 2011), TIP1.1-GFP (Gattolin et al, 2011), and GFP-AGP4 (Martinière et al, 2012).…”
Section: Transient Transformation Of a Thaliana Seedlings By Vacuum mentioning
confidence: 99%